Swimming ability of cyprinid species (subfamily schizothoracinae) at high altitude - Cai, Lu; Huang, Yingping; Johnson, David; Li, Minne; Liu, Rui; Hu, Wangbin; Jin, Yao; Chen, Xiaojuan; Tao, Jiangping; Zou, Xuan; Hou, Yiqun (Frontiers in Physiology, 2023)
The primary objective of this investigation was to study the effect of altitude on fish swimming ability. Different species were tested to ensure that the differences observed are not associated with a single species. Fish critical swimming speed and burst speed were determined using stepped-velocity tests in a Brett-type swimming respirometer. Based on the effects of water temperature and dissolved oxygen, it is clear that the swimming ability of fish decreases as altitude increases. Further, because the effects of high altitude on fish physiology go beyond the effects of lower temperature and dissolved oxygen, we recommend that fish swimming ability be tested at an altitude similar to the target fishway site to ensure the validity of fish data used for fishway design.